2019
DOI: 10.1111/pbr.12712
|View full text |Cite
|
Sign up to set email alerts
|

Genotype selection for physiological responses of drought tolerance using molecular markers in polycross hybrids of orchardgrass

Abstract: The present study aimed to assess the effect of contrasting levels of molecular and phenotypic diversity among polycross parents of orchardgrass on the performance of synthetic progeny with respect to physiological responses and drought tolerance. Four polycross groups each composed of six parental plants were evaluated under normal irrigation and drought stress conditions. A number of 923 inter simple sequence repeats and sequence related amplified polymorphism markers and several phenotypic traits were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The positive correlation between DFY and STI under mild and intense drought stress indicated that selection based on higher STI would lead to genotypes with higher yield and drought tolerance. Stability of production is one of the main breeding objectives in breeding for stress environments in perennial grasses (Abtahi et al., 2019). However, a negative relationship was found between STI and PE under mild and intense drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between DFY and STI under mild and intense drought stress indicated that selection based on higher STI would lead to genotypes with higher yield and drought tolerance. Stability of production is one of the main breeding objectives in breeding for stress environments in perennial grasses (Abtahi et al., 2019). However, a negative relationship was found between STI and PE under mild and intense drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a higher level of polymorphism ranging between 11 and 88%, with an average of 51.4%, was recorded using 12 primers in the global 12 examined wheat cultivars. In this connection, about 923 ISSR and sequence-related amplified polymorphism (SRAP) molecular markers, besides numerous phenotypic traits were employed to monitor triggered improvement of orchadgrass polycross populations subjected to water deficit conditions [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…SCoT uses a single 18-mer primer in a polymerase chain reaction (PCR) assays and requires an annealing temperature of 50 °C [ 14 ]. The ISSR and SCoT polymorphism has been used in genetic resource differentiation, cultivar characterization, and marker-assisted breeding programs in many plants; examples include alfalfa and Egyptian clover [ 15 ], Nigella sativa [ 16 ], Medicago sativa [ 17 ], Pistacia lentiscus [ 18 ], Moringa oleifera [ 19 ], Lathyrus species [ 20 ], Crepidium acuminatum [ 21 ], maize [ 22 ], Hordeum [ 23 ], and smooth bromegrass [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%